ҚАРАУЫЛБЕК ҚАЗИЕВ ТУЫНДЫЛАРЫНДАҒЫ ТУҒАН ЖЕР ТАБИҒАТЫНЫҢ КӨРІНІСІ. (Eurasian Journal of Philology Science and Education, 2015)
В статье исследуются особенности произведениймастера словесного искусства К. Казиева.This article is devoted to the research of the writerKaziev's descriptions of an unclouded childhood, flamingyouth, the nature of Kerbulak. The master of oral art K. Kazievdescribes the beauty of nature, latitude of an own steppe withpeculiar sensuality and tender motive.